ISTRI BEKERJA SEBAGAI PENCARI NAFKAH DITINJAU DARI PERSPEKTIF FEMINIS - Suryati; Prosawita Ririh Kusumasari; Ferryani Krisnawati (Collegium Studiosum Journal, 2023)
Articles 31 to 34 explain that the responsibility for providing maintenance for the wife lies with the husband, and it is also explained in Article 31 that each party has the same rights before the law, then the husband is the head of the family and the wife is the housewife, then Article 34 explained that the husband is obliged to protect his wife and the wife is obliged to manage the household as well as possible. According to feminists, it defines marriage for women and men equally, so that the division of research between women and men causes women's rights to be unequal in society. Because women are not considered the main breadwinners, these provisions also place the wife economically and emotionally dependent on her husband. The purpose of this research is to find out the feminist view of the wife's work as the breadwinner for the family. This research method uses normative juridical. The data used in this study are secondary data as the main data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data obtained was then analyzed qualitatively. The conclusion is that the views of feminists on the role of the wife as breadwinner, in this case men are responsible for earning a living in order to meet the needs of the household or family. This division of roles between women and men causes women's rights to be unequal in society. Because women are not considered the main breadwinners, the affirmation of the husband as the head of the family and the wife as a housewife in Law Number 1 of 1974 which was revised by Law Number 16 of 2019 concerning Marriage according to feminists is a tightening/restriction of the wife's functions and husband strictly. This provision also places the wife economically and emotionally dependent on her husband.